Feasibility Study Area and Dissolved Oxygen Carrying Capacity of Silvofishery Pond on the Coastal Area - Mardiana, Tri Yusufi; Ariadi, Heri; Rattanavichai, Wutti; Soedibya, Petrus Hary Tjahja; Linayati, Linayati (Marine Science Department Diponegoro University, 2024)
The aim of this research are to assess the feasibility of water and soil quality in silvofishery cultivation areas and to determine the environmental carrying capacity of the cultivation. The methods employed include Water Quality Index (WQI), Soil Quality Index (SQI), carrying capacity, and correlation analysis of parameters. The concentration of COD in the silvofishery pond water ranges from 705.34-749.50 mg.L-1, and the total nitrogen content in the soil ranges from 7-8 mg.L-1. The COD parameter in water shows a strong correlation with dissolved oxygen. The soil type parameter silt is correlated with redox potential, while the clay soil type is correlated with sand soil. The variance in data for water and soil quality variables is considered significant as per cluster analysis. The WQI values range from 0.47-0.85, categorized as poor, good, and excellent. The SQI values range from 0.52-0.77, falling into the good and excellent categories. The carrying capacity of dissolved oxygen ranges from 0.7-1.99 kg.ha-1, indicating that if the DO concentration is below this range, oxygen depletion may occur in the silvofishery pond. The research results indicate that the water and soil quality in the silvofishery pond is still sufficiently suitable for silvofishery activities. The carrying capacity of dissolved oxygen in the silvofishery pond is deemed adequate for operational silvofishery activities, ranging from 14.26-15.87 kg.ha-1. This implies that the silvofishery cultivation system is capable of enhancing aquaculture productivity while minimizing environmental pollution in the surrounding aquatic areas resulting from the waste generated during aquaculture operations.